The stages of constitutional nihilism development in Russia - Tatiana V. Rekhacheva (Правоприменение, 2020)
The subject. The paper concentrates on problem of development constitutional nihilism in Russia.The purpose of the article is confirmation or confutation of the hypothesis that we can distinguish four legal periods in the development of constitutional nihilism in Russia, taking into account its criteria.The methodology of study includes historical analysis of legal literature and formal legal analysis of normative legal acts.The main results and scope of their application. The concept of constitutional nihilism is debatable. There is no single definition of constitutional nihilism. The paper analysis main definitions Russian and foreign scientists and offer new integrating definition. The criteria of constitutional nihilism are very similar to criteria of legal nihilism but there are several exceptions. Еhe following grounds for classifying constitutional nihilism are most informative: level of prevalence; the nature of the external manifestation; the nature of denial; orientation of the nihilistic attitude, subjects of negation. At various stages of Russia's development, the main social groups among which constitutional nihilism was widespread were senior civil servants, high rank military officials and even presidents and even Emperor’s family. The object of constitutional nihilism is the denial and non-fulfillment of con-stitutional norms, non-participation in the implementation of constitutional relations. Constitutional nihilism in Russia is closely intertwined with constitutional upheaval, conspiracy, and rebellion. Constitutional nihilism is dangerous not only because it changes the structure of the state, but also because of the surge of legal nihilism among the population of the country. The sources of constitutional nihilism are periods of upheaval and other negative events that push the highest echelons of power to deliberately violate the laws.Conclusions. There are four main period of constitutional nihilism in Russia. The table compiled by the author contains six historical periods and four legal periods. Each of them is based on criteria of constitutional nihilism. The next period of constitutional nihilism can be calculated, because most often it occurs after large-scale social upheavals, but with the arrival of a strong and influential leader of the country, constitutional nihilism disappears for a while.